2001
DOI: 10.1136/pmj.77.914.753
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the understanding and treatment of chronic anal fissure

Abstract: Background-Chronic anal fissure is a common and painful condition associated with internal anal sphincter hypertonia. Reduction of this hypertonia improves the local blood supply, encouraging fissure healing. Surgical sphincterotomy is very successful at healing these fissures but requires an operation with associated morbidity. Temporary reduction in sphincter tone can be achieved on an outpatient basis by applying a topical nitric oxide donor (for example, glyceryl trinitrate) or injecting botulinum toxin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…bleeding, pain, prolapse and/or discharge per rectum were included, so the high prevalence of anal fissure was expected. According to a study carried out in proctology clinic 10% patients were found to be affected with anal fissure [11] which is somewhat closer to our data.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…bleeding, pain, prolapse and/or discharge per rectum were included, so the high prevalence of anal fissure was expected. According to a study carried out in proctology clinic 10% patients were found to be affected with anal fissure [11] which is somewhat closer to our data.…”
Section: Discussionsupporting
confidence: 76%
“…Included patients were also asked about their bowel habits as trauma due to the passage of hard stool, as in constipation, is thought to be and mentioned in many texts as an important initiating factor for the development of anal fissure [1,3,5,[7][8][9]11]. In our study out of 65 anal fissure patients, 48 were found to be with constipation and 17 were not.…”
Section: Discussionmentioning
confidence: 95%
“…This pressure would not be great enough to overcome the high resting anal pressure (90 mmHg) observed in anal fissure patients. As a result, the blood flow to fistula area would be decreased, preventing its healing 15 . Schouten et al 16 defined an inverted correlation between irrigation of the posterior midline and maximum resting anal pressure in both health and anal fissure patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction by Eisenhammer in 1951, lateral internal sphincterotomy has been used with increasing frequency and it is now considered the treatment of choice for chronic anal fissures. [19][20][21][22][23][24][25] The administration of pharmacological preparations that relaxes the internal anal sphincter effectively reducing anal pressure, can lead to healing of chronic fissures. However, this effect on the muscle is reversible and resting pressures appear to return to original values once treatment is discontinued, even after the fissure has healed.…”
Section: Discussionmentioning
confidence: 99%